Peningkatan Kapasitas Produksi Malen Woodycraft melalui Penerapan Alat Produksi Modern dalam Seni Ukir Kayu Bali - Lamopia, I Wayan Gede Lamopia; Riza Wulandari; Lilis Yuningsih; Ni Luh Putu Sukmayani; I Kadek Dimas Jaya Mahendra (Insan Kreasi Media, 2025)
Malen Woodycraft is an Micro Small and Medium Enterprises (MSME) that focuses on selling wood carvings. This MSME is located in a city that is famous for its handicrafts. The purpose of this community service is to solve the problem faced by Malen Woodycraft, namely the lack of production capacity in business development, which has so far still used manual tools. This causes a lack of efficiency and effectiveness in creating carving artwork. This activity uses the Participatory Action Research method with Social Return on Investment evaluation. The result of this service is the provision of production equipment assistance in the form of a Jigsaw Machine and a Compressor Machine with the Speed H&L 6188 Lakoni brand. With the provision of Jigsaw tools, craftsmen can cut wood with higher precision and in less time. Meanwhile, the use of a paint compressor can produce smooth and even coloring so that through the application of science and technology, this production tool can improve the quality and quantity of wood carving products according to market segmentation.